Gender and classroom interaction : an analysis of how a female and a male teacher in two EFL classrooms in Turkey give their attention to students - Bağ, Ebru. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The present study aimed to examine teachers’ classroom interaction with female and male students, and to reveal the teachers’ and the students’ perceptions about gender and classroom interaction in EFL classrooms in Turkey. More specifically, a female and a male teachers’ classrooms were examined to see whether there were any similarities and/or differences in the level of the teachers’ student selection, in the number of the teachers’ academic (A) and non-academic (NA) initiating moves directed towards female and male students, and in the amount of the feedback provided to female and male students by the teachers. For the study, two EFL classrooms, taught by a female and a male teacher at a preparatory school of a university, were video-taped and observed for two months. Both the teachers and some of the students were interviewed at the end of the data collection process. The transcribed classroom data were analyzed using an adaptation of the Sinclair and Coulthard (1992) Classroom Discourse Analysis Model. The findings of the study showed that both the female and the male teacher did not pay equal attention to female and male students with respect to teacher’s initiating moves (both academic and non-academic) and teacher’s academic (A) and non-academic (NA) initiating moves. As for the feedback provided to female and male students provided by the teachers, the results showed that the female teacher provided equal attention to female and male students while the male teacher did not pay equal attention. The findings of the interviews, all of the students who were interviewed for the study indicated that the teachers select equal number of female and male students to participate in the classroom interaction. During the interview with the teachers, the female teacher stated that while selecting students to talk, she paid attention to the academic capacity of the students to answer the questions and the distribution between girls and boys, while the male teacher indicated that he paid attention to the readiness of the students to answer the questions. The results of the study were discussed by referring to the relevant literature, and pedagogical implications were drawn.
Keywords: English language -- Study and teaching.; Language teachers -- Training of.